PENERAPAN MODEL PENDIDIKAN METEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 49 TAMERAN KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Akmar, Maisa; Syahrilfuddin, Syahrilfuddin; Lazim, Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the weakness of student’s learning result of mathematics subject. It show from 30 student’s, 18 students (60%) have lower score, and it is only 12 student’s (40%) have average score 65. The KKM of this school is 70. According to that problem, the research by implementing Classroom Action Research method (CAR) with implementation indonesian realistic mathematics education (PMRI). In cycle I, the persentage of teachers activity in first is adguate 48,1%. In second meeting, teachers activity significantly increased to 75% with good category. In cycle 2, first meeting was in very good category 84,6% and second meeting indicated a very goood category 86,5%. Mean while, the activity of student’s also improved. In cycle I indicated 44,2% in educated category and in cycle 2 has increased up to 76,9% with good category. In cycle 2, first meeting, the activity of student’s has been increasing to 78,8% with goog category and second meeting indicated veri good category 82,7%. An average score of student’s learning result before impementation is 65. It increased to 67,3 in cycle I, and 72 in cycle 2. In conclussion, implementation indonesian realistic mathematics education model can improve student’s learning result of three grade students of SD Negeri 49 Tameran Kecamatan Bengkalis Kabupaten Bengkalis in mathematics subject.Key word: PMRI, Learning result of mathematic subject.